PENGARUH SIKAP BELAJAR TERHADAP HASIL BELAJAR PADA MATA PELAJARAN EKONOMI DI SMA KEMALA BHAYANGKARI - Hulan, Hulan; Khosmas, Khosmas; Genjik, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis thesis entitled "the influence of learning attitudes toward student learning outcomes on economic subjects class XI IIS 3 SMA Kemala Bhayangkari Sungai Raya District Kubu Raya". The problem of this research is (1) How is the attitude of student learning class XI IIS 3 SMA Kemala Bhayangkari Kubu Raya on economic learning? (2) How is the result of student learning class XI IIS 3 SMA Kemala Bhayangkari on economic learning? (3) Is there an influence between students' learning attitudes toward learning outcomes on economic subjects? The method used is descriptive method in the form of relationship studies. The sample of this research is students of class XI IIS 3 SMA Kemala Bhayangkari Kubu Raya as many as 32 students. In hypothesis test that is t test> t table or 5,462> 2,042 meaning there is influence between attitude study and result learn. R result of 0.100 according to predetermined conditions, this figure lies between 0,00-0,199 which belongs very low category. The output value of R2 shows the number of 0.10, meaning the percentage of the contribution of learning attitudes toward student learning outcomes by 10% while the rest is influenced by other factors.Â Keywords: learning attitudes, learning outcomes, economic subjects